Analysis of risk factors for prolonged intensive care unit stay after colorectal cancer surgery - Song, Xuefeng; Liu, Yabin; Dong, Biao (Frontiers in Oncology, 2026)
ObjectiveThis study employed a retrospective analysis to investigate the risk factors associated with prolonged intensive care unit (ICU) stay following colorectal cancer surgery.MethodsA total of 325 patients who underwent colorectal cancer surgery and were subsequently transferred to the ICU at the Fourth Hospital of Hebei Medical University were enrolled as the colorectal cancer group. The ICU length of stay (LOS) was stratified by quartiles, with the 75th percentile (≥61 hours) defined as the prolonged ICU stay group. Basic information, preoperative comorbidities, surgical details, and postoperative complications were compared between the two groups. Univariate and multivariate analyses were performed to identify risk factors for prolonged ICU stay. The predictive ability of the model was evaluated using the area under the receiver operating characteristic (ROC) curve (AUC). Calibration curves were used to assess the agreement between predicted and observed outcomes, and decision curve analysis (DCA) was conducted to evaluate the net benefit for patients.ResultsAmong the 325 enrolled patients (median age 77 years), 183 (56.3%) were male and 142 (43.7%) were female. The cohort was divided into a normal group (n = 243) and a prolonged group (n = 82). Univariate analysis identified preoperative obstruction, preoperative perforation, Class IV surgical incisions, open surgical approach, intraoperative blood loss, duration of mechanical ventilation, perioperative sepsis, perioperative acute kidney injury (AKI), lower extremity deep vein thrombosis (DVT), and mean postoperative platelet count, albumin, and blood urea nitrogen levels within the first 24 hours of ICU admission as risk factors for prolonged ICU stay. After adjusting for confounding factors, multivariate logistic regression analysis revealed that the laparotomy, perioperative sepsis, postoperative duration of mechanical ventilation, occurrence of lower extremity DVT, and mean platelet count within the first day of ICU admission were independent risk factors for prolonged ICU stay. The AUC of the ROC curve was 0.8081 (95% confidence interval [CI]: 0.745–0.870), indicating strong discriminatory ability. The calibration curve demonstrated excellent agreement between predicted and observed outcomes (observed-to-expected [O:E] ratio = 1.000, calibration-in-the-large [CITL] = -0.000, slope = 1.000). Bootstrap validation yielded a Brier score of 24.1%, a concordance statistic (C-statistic) of 0.772, an E:O ratio of 0.981, a slope of 0.756, and a CITL of 0.029. DCA revealed a high net benefit for predicting prolonged ICU stay at lower threshold probabilities. Subgroup analysis by surgical site (left-sided vs. right-sided colon cancer) showed AUCs of 0.7892 (95% CI: 0.71–0.87) for left-sided colon cancer and for right-sided colon cancer of 0.8253 (95% CI: 0.72–0.93).ConclusionThe laparotomy, perioperative sepsis, postoperative duration of mechanical ventilation, occurrence of DVT, and mean platelet count within the first day of ICU admission were independent risk factors for prolonged ICU stay following colorectal cancer surgery.